A COMPUTER TOOL FOR TRAINING PILOTS’ LISTENING SKILLS IN AVIATION ENGLISH - Olena I. Moskalenko; Oleksandr V. Didenko (Інформаційні технології і засоби навчання, 2018)
A methodology of training pilots’ listening skills by means of a computer tool is highlighted in the article. Various computer exercises are used to enhance the learners’ level of English as well as improve their listening skills. English is one of the crucial factors influencing flight safety; pilot’s ability to listen, hear, interpret and react to controller’s information in English is of paramount importance during radio communication. It is emphasized that the development of computer software and appearance of new computerized tools predetermine the search for new methods of teaching Aviation English to future pilots and air traffic controllers. One of the ways how to enhance the level of professional training is implementation of ICT in the teaching and learning process. Computer technologies and technical means of language training can simulate the flight situations that a pilot may encounter during his/her professional activity. In the article the authors demonstrate one of the useful methods – application of a computer tool for training listening skills in Aviation English. The computer tool is aimed at training pilots’ listening skills. It can be used to prepare students for achieving ICAO Operational Level (Level 4) or higher according to the ICAO Language Proficiency Requirements. It consists of six tasks based on general aviation English and phraseology of radio communication. Based on the proposed methodology the experiment with Aviation graduate students was carried out, which was based on the implementation of the computer tool into the course «Phraseology of radio communication». Listening skills’ assessment was conducted according to three criteria: cognitive (knowledge), operational (skills), psychological (abilities) and their descriptors. According to the level of listening skills three levels – low, medium and high were differentiated. The results of the experimental study indicate that there have been positive changes in the distribution of students’ levels of listening skills in the phraseology of radio communication in English with the introduction of the computer tool: the number of students with high- and medium-level of listening skills increased whereas that of low-level listening skills decreased.